Some existence results for systems of impulsive stochastic differential equations - Mekki, Sliman; Blouhi, Tayeb; Nieto, Juan J.; Ouahab, Abdelghani (Annales Mathematicae Silesianae, 2021)
In this paper we study a class of impulsive systems of stochastic differential equations with infinite Brownian motions. Sufficient conditions for the existence and uniqueness of solutions are established by mean of some fixed point theorems in vector Banach spaces. An example is provided to illustrate the theory.